Choline supplements: An update - Kansakar, Urna; Trimarco, Valentina; Mone, Pasquale; Varzideh, Fahimeh; Lombardi, Angela; Santulli, Gaetano (Frontiers in Endocrinology, 2023)
Choline alfoscerate (C8H20NO6P), also known as alpha-glycerophosphocholine (α-GPC, or GPC), is a cholinergic compound and precursor of acetylcholine. GPC is extensively used as a food supplement. In this review, we will examine the main preclinical and clinical investigations assessing the effects of GPC. Additionally, there are other different forms of choline supplementation currently available, including choline bitartrate, lecithin, and citicoline, which have been shown to represent an effective strategy for boosting memory and enhancing cognitive function.